Nephron-Sparing Surgery for Upper Urinary Tract Urothelial Carcinoma - Sung Han Kim; Ilma S. Savul; Seth P. Lerner (Journal of Urologic Oncology)
Radical nephroureterectomy (RNU) remains the gold standard for the surgical management of upper tract urothelial carcinoma (UTUC) from the ureterovesical junction to the renal pelvis. However, the removal of the ipsilateral intact kidney causes morbidity due to renal functional deterioration after RNU. Recently, the indications for nephron-sparing surgery (NSS) in UTUC have been expanded to preserve the intact kidney. Minimally invasive surgical approaches, including endourological, laparoscopic, and robotic-assisted techniques for segmental resection of the distal ureter with ureteral reimplantation have shown favorable oncological and clinical outcomes (for both noninvasive and invasive ureteral tumors). The established guidelines for UTUC have limited indications for NSS. Because of low tumor burden, stage Ta/T1 UTUC is considered the best indication for NSS. NSS requires close follow-up and managing the risk of recurrence in the preserved ipsilateral ureter and/or renal pelvis. To overcome these limitations, adjuvant administration of various immuno-chemotherapeutic agents is being explored to overcome the resistance to therapeutic cell death and evasion of immune destruction from current therapies with better prognostic outcomes. The aim is to reduce urothelial cancer recurrence improving the effectiveness of NSS and to achieve comparable outcomes to RNU in UTUC. In this review article, we have comprehensively discussed the different types of NSS in UTUC, the indications for NSS in the international guidelines, and oncological outcomes of each of the NSS techniques.